A comprehensive review on polarity, partitioning, and interactions of phenolic antioxidants at oil–water interface of food emulsions. Issue 5 (30th June 2021) - Farooq, Shahzad; Abdullah; Zhang, Hui; Weiss, Jochen
Abstract: There has been a growing interest in developing effective strategies to inhibit lipid oxidation in emulsified food products by utilization of natural phenolic antioxidants owing to their growing popularity over the past decades. However, due to the complexity of emulsified systems, the inhibition mechanism of phenolic antioxidants against lipid oxidation is rather complicated and not yet fully understood. In order to highlight the importance of polarity of phenolic antioxidants in emulsified systems according to the polar paradox, this review covers the recent progress on chemical, enzymatic, and chemoenzymatic lipophilization techniques used to modify the polarity of antioxidants. The partitioning behavior of phenolic antioxidants at the oil–water interface, which can be influenced by the presence of synthetic surfactants and/or antioxidant emulsifiers (e.g., polysaccharides, proteins, and phospholipids), is discussed. In addition, the emerging phenolic antioxidants among phenolic acids, flavonoids, tocopherols, and stilbenes applied in food emulsions are elaborated. As well, the interactions of polar–nonpolar antioxidants are stressed as a promising strategy to induce synergistic interactions at oil–water interface for improved oxidative stability of emulsions.